Comparative Analysis of Implementation Strategies and Readiness for Smart Village Developmen: A Study in Pangandaran Village and Wonoharjo Villa (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to analyze the implementation of smart villages in Pangandaran Village, the readiness for development in Wonoharjo Village, and the strategies for their respective smart village initiatives. A quasi-qualitative method was used in the research. The results show that the implementation of smart villages in Pangandaran Village is unbalanced, with a primary focus on Human and ICT dimensions, while other sectors like Economy, Energy, and Tourism are less emphasized. In contrast, Wonoharjo Village's readiness for smart village development is dominated by ICT infrastructure, especially internet connectivity, which remains a concern due to limited coverage. To optimize the Nusantara Smart Village initiative, the study suggests enhancing the capacity of village officials, supporting SPBE (E-Government) through the Communication and Information Agency, and ensuring strong leadership commitment. These factors are crucial for Pangandaran Village to develop a comprehensive and sustainable Smart Village. For Wonoharjo Village, the development strategy should focus on leveraging external government programs and accelerating the digital-based economic potential. Both villages need to prioritize strengthening ICT infrastructure and enhancing the capacity of village officials. With this integrated approach, Wonoharjo Village is expected to transition from readiness to a Smart Village, providing efficient public services and fostering economic and social sustainability.